Evaluation of Adult Community Supervision Strategies in Multnomah County, Oregon, 1995, 1998, and 2000 Cohorts - Johnson, Kelly Dedel ([Verlag nicht ermittelbar], 2003)
This study was undertaken to determine whether a new form of community supervision in Multnomah County, Oregon, had been properly implemented and to determine its impact on public safety, as well as to assess recidivism rates in light of the revised supervision. A quasi-experimental design was employed using non- randomized comparison groups consisting of offenders admitted to community supervision in Multnomah County, Oregon, in 1995, 1998, and 2000. Administrative records data were collected from the Oregon Department of Corrections, Multnomah County Department of Community Justice, Portland Police Departments, Multnomah County Sheriff, the District Attorney's office, and court records.